STUDENTS’ OPINIONS TOWARD WRITING ACTIVITIES - Sanaria Maneba (English Education Journal, 2019)
Problem in this research is how is students’ opinions toward writing activities. This research is a qualitative research. The subject of the research is First semester consisted of 21 students who pragrammed Basic Writing subject in English Study Program at Dayanu Ikhsanuddin University, academic year 2019-2020. The instrument used in this research is questionairre about students’ opinion toward writing activities. The test consisted of 10 numbers with 5 optional degree of feeling, are: Strongly Agree (5), Agree (4), Neither Agree nor Disagree (3), Disagree (2) and Strongly Disagree (1). Data analysis uses the percentage formula as the frequency is divided by the number of the students, then the total number of the percentage is multiplied by 100% (Sugiyono,2010 in Husain, 2012).1 The research outcomes is majority students at the first semester of English Study Program, Teaching Training and Education Faculty, Dayanu Ikhsanuddin University, academic year 2019/2020 presented their positive opinion and responses toward writing activities.